FAKTOR - FAKTOR YANG MEMPENGARUHI STATUS GIZI ANAK BALITA DI DESA SIMANGALAM KECAMATAN KUALUH SELATAN KABUPATEN LABUHANBATU UTARA - HENNY ARWINA BANGUN; DONAL NABABAN; EVAWANI MARTALENA (JURNAL ILMIAH SIMANTEK, 2020)
Most nutritional problems in Indonesia include less nutrition or that include an unbalanced array of dishes as well as overallconsumption that does not provide adequate body requirements. Toddler (1-5 years) is the age group most often suffer frommalnutrition or is one of the vulnerable community groups. Research aims to determine the factors that affect the nutritionalstatus of toddlers in the village of Simangalam District Kualuh Selatan South regency of North Labuhanbatu. Types ofanalytical research with cross sectional. The population is a mother who has children aged 12-59 months in Simangalamvillage for 230 people. Samples using purposive sampling is 70 mothers who have toddlers with age 12-59 months. Theresults of the study are known to influence the historical factors of infectious diseases (P = 0,000), maternal work (P =0,004), number of children (P = 0,000), family income (P = 0,000), maternal knowledge (P = 0,000) and parenting children (P= 0,000) to the nutritional status of children in the village of Simangalam subdistrict Kualuh Selatan Regency. In advice forhealth workers through POSYANDU activities to improve health counseling, especially about balanced nutrition and fosterpatterns for toddlers who experience poor nutrition and malnutrition.